2003
DOI: 10.1159/000070088
|View full text |Cite
|
Sign up to set email alerts
|

Loading-Related Subjective Symptoms during a Vocal Loading Test with Special Reference to Gender and Some Ergonomic Factors

Abstract: Vocal loading-related subjective symptoms were studied in a day-long vocal loading test. The voices of 40 female and 40 male voluntary young students were loaded by having them read aloud a novel for five times 45 min. The subjective symptoms that occurred during the vocal loading session were reported by filling in a questionnaire after each session. The responses loaded on five factors in a factor analysis: (1) ‘central fatigue’; (2) ‘symptoms of the neck, shoulders and back’; (3) ‘drying in the mouth and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 26 publications
4
33
0
1
Order By: Relevance
“…Subjectively, previous studies have shown a significant increase in self-rated voice symptoms during the working day 3,6,9 or after a loading task performed in a laboratory. 10,16,17,32 Effects of intensity level as voice loading factor Voice intensity changes with the amplitude of vocal fold's oscillations, influencing the distance dose and the dissipated energy dose. 14,31 Voice intensity affects the shear stress in the ligament 33 and the medial compression of the vocal folds (compressive stress).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjectively, previous studies have shown a significant increase in self-rated voice symptoms during the working day 3,6,9 or after a loading task performed in a laboratory. 10,16,17,32 Effects of intensity level as voice loading factor Voice intensity changes with the amplitude of vocal fold's oscillations, influencing the distance dose and the dissipated energy dose. 14,31 Voice intensity affects the shear stress in the ligament 33 and the medial compression of the vocal folds (compressive stress).…”
Section: Introductionmentioning
confidence: 99%
“…36 Effects of both duration and intensity level on voice Few studies have observed the effect of both intensity level and duration of the loading task. Vintturi et al 18,32 studied the changes in voice during a vocal loading test with, among others, a specific emphasis on the speech output level. Neils and Yairi 40 examined the influence of various levels and durations of noise exposure in six females reading in noise during 45 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic dehydration of the body, as well as superficial dehydration of the vocal tract, such as may occur through oral breathing or conditions of low humidity, contributes to increases in perceived vocal effort [14,34,35]. This increase in perceived vocal effort is likely related to an increase in PTP [34]. As previously discussed, reduced hydration contributes to an increase in vocal fold viscosity, thus decreasing mobility and increasing the muscular effort required to phonate [13].…”
Section: Discussionmentioning
confidence: 98%
“…Systemic dehydration of the body, as well as superficial dehydration of the vocal tract, such as may occur through oral breathing or conditions of low humidity, contributes to increases in perceived vocal effort [14,34,35]. This increase in perceived vocal effort is likely related to an increase in PTP [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation